Covid-19 and the role of smoking: the protocol of the multicentric prospective study COSMO-IT (COvid19 and SMOking in ITaly). - Cattaruzza, Maria Sofia; Gorini, Giuseppe; Bosetti, Cristina; Boffi, Roberto; Lugo, Alessandra; Veronese, Chiara; Carreras, Giulia; Santucci, Claudia; Stival, Chiara; Pacifici, Roberta; Zagà, Vincenzo; Gallus, Silvano; et al. (Acta Biomedica Atenei Parmensis, 2020)
The emergency caused by Covid-19 pandemic raised interest in studying lifestyles and comorbidities as important determinants of poor Covid-19 prognosis. Data on tobacco smoking, alcohol consumption and obesity are still limited, while no data are available on the role of e-cigarettes and heated tobacco products (HTP). To clarify the role of tobacco smoking and other lifestyle habits on COVID-19 severity and progression, we designed a longitudinal observational study titled COvid19 and SMOking in ITaly (COSMO-IT). About 30 Italian hospitals in North, Centre and South of Italy joined the study. Its main aims are: 1) to quantify the role of tobacco smoking and smoking cessation on the severity and progression of COVID-19 in hospitalized patients; 2) to compare smoking prevalence and severity of the disease in relation to smoking in hospitalized COVID-19 patients versus patients treated at home; 3) to quantify the association between other lifestyle factors, such as e-cigarette and HTP use, alcohol and obesity and the risk of unfavourable COVID-19 outcomes. Socio-demographic, lifestyle and medical history information will be gathered for around 3000 hospitalized and 700-1000 home-isolated, laboratory-confirmed, COVID-19 patients. Given the current absence of a vaccine against SARS-COV-2 and the lack of a specific treatment for -COVID-19, prevention strategies are of extreme importance. This project, designed to highly contribute to the international scientific debate on the role of avoidable lifestyle habits on COVID-19 severity, will provide valuable epidemiological data in order to support important recommendations to prevent COVID-19 incidence, progression and mortality.